Análisis Molecular de las Mutaciones 2299delG y C759F en Individuos Colombianos con Retinitis Pigmentosa e Hipoacusia Neurosensorial (2015)
Objective: To determine the presence of 2299delG and C759F mutations in 37 non-related subjects from Colombia suffering from RP and sensorineural deafness. Materials and methods:Exon 13 of USH2A gene was directly sequenced in all subjects selected for the study. Results: In this work, the 2299delG mutation was only observed in subjects suffering from Usher syndrome type II while the C759F mutation was not detected in any subject.